2018
DOI: 10.1080/10837450.2018.1479866
|View full text |Cite
|
Sign up to set email alerts
|

Using dextran of different molecular weights to achieve faster freeze-drying and improved storage stability of lactate dehydrogenase

Abstract: Freeze-drying of protein formulations is frequently used to maintain protein activity during storage. The freeze-drying process usually requires long primary drying times because the highest acceptable drying temperature to obtain acceptable products is dependent on the glass transition temperature of the maximally freeze-concentrated solution (T'). On the other hand, retaining protein activity during storage is related to the glass transition temperature (T) of the final freeze-dried product. In this study, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Clearly the viscosity decreases with temperature, and the carbohydrate glass viscosity is larger than that of the sugar glass. The latter can be explained, when considering the glass transition temperature (Tg) of the different components of the blends as found in literature [24][25][26], shown in Table 1. This shows that dextran has a higher Tg compared to sucrose and dextrose.…”
Section: Rheology Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly the viscosity decreases with temperature, and the carbohydrate glass viscosity is larger than that of the sugar glass. The latter can be explained, when considering the glass transition temperature (Tg) of the different components of the blends as found in literature [24][25][26], shown in Table 1. This shows that dextran has a higher Tg compared to sucrose and dextrose.…”
Section: Rheology Resultsmentioning
confidence: 99%
“…Further research should look into a method for determining the Tg of the blend as well as a method for determining the water content of the sugar glass blends, verifying the expected little to no water content. With these methods at hand a more extensive investigation can be performed, which could include a wider variety in molecular weight of dextran as well as sugar alcohols and their effect on the blend and associated printing properties [21,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that the T g of dextrans increases with increasing M w up to around 40 kDa, after which a further increase in M w did not result in a significant further increase in the T g [ 13 ]. Similarly, the T g of PVP only increased with increasing M w up to around 360 kDa (see Table 1 and Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, polymers with higher M w may require longer milling times to obtain an ASD during milling. In this regard, it has been shown that the relationship between the increasing glass-transition temperature (T g ) and the increasing M w of a polymer only applies up to a critical M w , above which the T g does not increase further [12,13]. Since the T g /M w of a polymer is also indirectly a measure of the molecular mobility of the polymer, this study aims to investigate the putative correlation between the molecular mobility (T g /M w ) of a polymer and the ball-milling amorphization kinetics (t a ) of different grades of dextran and PVP, and the two model drugs IND and chloramphenicol (CAP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation